The Influence of Firm Size, Capital Structure, Liquidity, Profitability, And Asset Structure on Firm Value : A Study on Manufacturing Companies in The Infrastructure Sector Listed on The Indonesia Stock Exchange (IDX) For the Period 2020-2023 - Situmorang, Lilis Farida; Pratama, Su Novianti Suci; Wulandari, Bayu; Habibie, Muhammad (International Journal Of Economics Social And Technology (IJEST), 2025)
This research aims to find out influence in a way partial from size company capital structure liquidity profitability and structure assets to mark company to company manufacturing in the sector infrastructure listed on the Indonesia Stock Exchange for the period 2020-2023. The population as many as 70 companies but that fulfills criteria research that can made into sample study as many as 17 companies. The sampling technique sample study that is using purposive sampling. The type of data used in this study is secondary data. The results of this study indicate that size company capital structure liquidity profitability and structure assets in a way simultaneous influential to mark company. In partial size the company has no influence in a way significant to mark company capital structure has an influence in a way significant to mark company liquidity has an influence in a way significant to mark company profitability has an influence in a way significant to mark company structure assets have influence in a way significant to mark company.